Use of photoactivatable peptide substrates of Saccharomyces cerevisiae myristoyl-CoA:protein N-myristoyltransferase (Nmt1p) to characterize a myristoyl-CoA-Nmt1p-peptide ternary complex and to provide evidence for an ordered reaction mechanism. - Rudnick, D A (1993)
Nmt1p (EC 2.3.1.97) catalyzes the transfer of myristate (C14:0) from coenzyme A to the N-terminal glycine residue of a variety of eukaryotic cellular and viral proteins. Our recent studies of the 455-amino acid Saccharomyces cerevisiae acyltransferase (Nmt1p) suggested that its mechanism of catalysis is ordered Bi Bi with myristoyl-CoA binding occurring prior to binding of peptide and release of CoA occurring prior to release of the myristoyl-peptide. The interaction between enzyme and peptide has now been examined in greater detail by using photoactivatable octapeptide substrates containing 125I-labeled azidosalicyclic acid attached via an amide bond to the gamma-amino group of a diaminobutyrate residue located at position 2 or the epsilon-amino group of a lysine residue located at position 8. The photopeptides can be specifically crosslinked to chymotryptic fragments of Nmt1p in the presence but not in the absence of a nonhydrolyzable myristoyl-CoA analog, S-(2-oxo)pentadecyl-CoA. Labeling of the chymotryptic fragments is markedly reduced when GLYASKLS, a high-affinity substrate derived from residues 2-9 of S. cerevisiae ADP-ribosylation factor 2, or ALYASKLS, a competitive inhibitor (for peptide), is added with the iodinated photopeptide. These findings suggest that peptide affinity for the acyl-CoA-Nmt1p binary complex is much greater than it is for apoNmt1p, consistent with the ordered Bi Bi mechanism ascribed to Nmt1p. Finally, automated sequential Edman degradation of these chymotryptic fragments suggests that the peptide binding domain of Nmt1p may be composed of elements from two protease-resistant domains, Arg42-Try219 and Thr220-Leu455.